Implementation of Children Nutrition Meeting Through Healthy Eating Program - Aerin, Wafa; Muqowim, Muqowim (Indonesian Journal of Early Childhood Education Studies, 2020)
Growth and development in children is greatly influenced by the intake of nutrients in food. During the period of growth and development, the provision of good nutrition is not always carried out perfectly. One of the influencing factors is the level of parental knowledge and children's preference on fast food. If feeding is always not in accordance with the needs of children, it will cause developmental problems in children. One of the efforts made to overcome these problems is a healthy eating program. This research was conducted with the aim to determine the results of nutrition fulfillment in early childhood through a healthy eating program. This research uses descriptive qualitative research methods. Research location in Al-Isyad Al-Islamiyyah Purwokerto Kindergarten. With research subjects include, teachers, Al-Irsyad Al-Islamiyyah Purwokerto Kindergarten students, parents, and school principals. Data obtained through observation, interviews, and documentation. The results of this study describe the implementation of the fulfillment of children's nutrition through a healthy eating program implemented at Al Irsyad Al Islamiyyah Purwokerto Kindergarten, this study also shows good menu variations in accordance with the nutritional needs of early childhood every day in healthy eating programs prepared by nutritionists, so as to improve nutritional status in children.